Optimalisasi Kesehatan dan Relaksasi Mahasiswa melalui Dreams Pillow Aromatherapy: Studi Simulasi di Institut Kesehatan Payung Negeri Pekanbaru - Malayka Agustina Putri Sipayung; Rena Afri Ningsih; Gadis; Riza Oktiana; Ayu Agustin; Kamisah; Ramadhani Isya Putri; Sonia Dalfia; Ratna Putri Hartati; Gifa Rahmanda; Nelly Oktaviani; Thasya Amanda; Fidia Oktaviani; Tania Margaretha Sitompul (TOLIS MENGABDI : Jurnal Pengabdian Kepada Masyarakat, 2025)
Insomnia is a common sleep disorder. Symptoms include difficulty sleeping, frequent awakenings, or waking up too early. There are several ways to overcome insomnia, one of which is a complementary approach. Insomnia can be overcome by doing acupressure massage at several acupressure points. Aromatherapy is also a way to treat insomnia. by using essential oils from plants which have calming properties and help the body relax. so the aim of this project is to develop a prototype of an aromatherapy pillow that is effective for treating insomnia. The method used is the Expert System Development Life Cycle (ESDLC), which consists of several stages, namely: Planning, analysis, design, implementation, testing and maintenance. This project begins with planning, preparing the team, namely determining ideas and partners for cooperation. Next, conduct a survey to collect data. Based on the survey results, a prototype of an aromatherapy pillow was designed and made. The pillow is designed by placing acupressure points on the pillow and combining it with lavender and lemongrass aromatics. After being produced, the pillow was tested on 5 respondents to get feedback and improvements were made if necessary. In the trials carried out there was a decrease in insomnia scores from respondents. The final stage is the evaluation of the entire project and preparation of a report. This product can help reduce insomnia and provide a sense of relaxation regarding insomnia. For this reason, we also hope that this product can be accepted by the public and can help other people's health. Keywords: Insomnia, acupressure, aromatherapy, pillow